IN VITRO GLUCOSE BINDING ACTIVITY OF TERMINALIA BELLIRICA - Das C, Mary Shoba; Devi S, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Herbal medicine has become an integral part of standard healthcares based on a combination of time honored traditional usage and ongoing scientific scrutiny of their therapeutic potential and safety. The petroleum ether, chloroform, ethanol, and aqueous extracts of leaves, fruits, and bark of Terminalia bellirica were evaluated for their effects on glucose adsorption, diffusion, and glucose transport across yeast cell. All the extracts could bind the glucose effectively, and the glucose binding capacity was directly proportional to the molar concentration of glucose. The rate of glucose diffusion across the membrane was found to increase from 30 to 180 minutes. The rate of uptake of glucose into the yeast cells was linear in all the five glucose concentration used in the study. Among the four extracts, ethanolic extract of leaves, fruits, and bark of T. bellirica show higher hypoglycemic activity while compared to other extracts. The hypoglycemic effect exhibited by the ethanol extracts of leaves, fruits, and bark is mediated by increasing glucose adsorption, glucose diffusion and glucose transport across the cell membrane as revealed by simple in vitro model of yeast cells. Keywords: Glucose adsorption, Glucose diffusion, Terminalia bellirica, Yeast cells. Â 